Avaliação dos processos de filtração por membranas e de adsorção na purificação de biodiesel - Alves, Magno José (2015)
Biodiesel is a biofuel that can be used as a substitute for petroleum diesel. One of the critical stages of the biodiesel production process with respect to its purification, which is usually performed by successive washes with clean water. This process, besides been expressive, results in the generation of a considerable amount of effluent to be treated later. Thus, the main objective of this research was to evaluate the process of membrane separation and adsorption process in Biodiesel purification. The first stage of this work consisted in the production of biodiesel via ethylic and metílicas routes, using refined soybean oil. As a raw material the biodiesel was then purified by conventional methods, washing with pure water, and processes using membranes. Then the effectiveness of polymeric microfiltration membranes and ultrafiltration membranes in biodiesel purification. Was evaluated flat polymeric microfiltration membranes were used, 0.22 μm pore diameter of cellulose ester, and polyethersulfone 0.05 μm pore diameter, and ceramic tubular ultrafiltration membranes, α-Al2O3/TiO2, 5 kDa and 20 kDa. Polymeric membranes were evaluated in a module that uses the principle of the perpendicular filtration, whereas ceramic membranes were tested using tangential filtration module. All membrane experiments were performed at room temperature. The microfiltration experiments were performed in two transmembrane pressures 0.5 bar to the membrane of 0.22 μm and 2.5 bar for the membrane of 0.05 μm. For the experiments performed using ultrafiltration membrane, the transmembrane pressure was set ad 4 bar. These pressures were chosen based on preliminary tests. The performance of the membranes was evaluated by glycerin retention capacity and the permeate flow values after stabilization. Besides filtration of the crude biodiesel, additional tests were performed with the addition of small volumes of water to the crude biodiesel. Deionized water was added to the biodiesel sample in weight proportions of 0.1 to 0.2%. The free glycerol content was reduced in all filtrations. However, between the membranes tested, the level of free glycerin (0.02 wt%) was achieved with the 5 kDa membrane.The addition of small amounts of water resulted in a significant increase in removal of free glycerin required by biodiesel legislation. In addition to the purification by membranes cleaning was evaluated for biodiesel purification. 9 alternative adsorbents were used (Amberlite XAD®-2; sugarcane bagasse, sugarcane bagasse blown sugar, bagasse ash; PVA; sulfonated PVA, cellulose acetate, chitosan and Polysulfone) and commercial (Magnesol® D 60) for removal of glycerin present in the biodiesel. The results showed that only PVA was not effective in reducing the glycerine level values stipulated by legislation (0.02 weight %), and sugar cane bagasse in natura showed the best results in terms of removing glycerin. The use of alternative adsorbents did not change the parameters density, viscosity and acid number of the biodiesel. The experimental kinetic data obtained for the best adsorbent were adjusted to intraparticle diffusion models and pseudo-second order, which indicates that the limiting factor for the rate of diffusion can be mass transfer and chemisorption. Thus, alternative methods of purification of biodiesel were efficient processes with relative low cost and low environmental impact.